Assessment of the intrarater and interrater reliability of an established clinical task analysis methodology. - Slagle J; Weinger MB; Dinh MT; Brumer VV; Williams K; Slagle, Jason; Weinger, Matthew B; Dinh, My-Than T; Brumer, Vanessa V; Williams, Kevin (Anesthesiology, 2002)
Background: Task analysis may be useful for assessing how anesthesiologists alter their behavior in response to different clinical situations. In this study, the authors examined the intraobserver and interobserver reliability of an established task analysis methodology.Methods: During 20 routine anesthetic procedures, a trained observer sat in the operating room and categorized in real-time the anesthetist's activities into 38 task categories. Two weeks later, the same observer performed task analysis from videotapes obtained intraoperatively. A different observer performed task analysis from the videotapes on two separate occasions. Data were analyzed for percent of time spent on each task category, average task duration, and number of task occurrences. Rater reliability and agreement were assessed using intraclass correlation coefficients.Results: Intrarater reliability was generally good for categorization of percent time on task and task occurrence (mean intraclass correlation coefficients of 0.84-0.97). There was a comparably high concordance between real-time and video analyses. Interrater reliability was generally good for percent time and task occurrence measurements. However, the interrater reliability of the task duration metric was unsatisfactory, primarily because of the technique used to capture multitasking.Conclusions: A task analysis technique used in anesthesia research for several decades showed good intrarater reliability. Off-line analysis of videotapes is a viable alternative to real-time data collection. Acceptable interrater reliability requires the use of strict task definitions, sophisticated software, and rigorous observer training. New techniques must be developed to more accurately capture multitasking. Substantial effort is required to conduct task analyses that will have sufficient reliability for purposes of research or clinical evaluation.